93.6k views
4 votes
(6 - t) + (7 - t) - (4 - t) = 0


How do you do this

1 Answer

3 votes
Remove the brackets
6 - t + 7 - t - 4 + t = 0

Eliminate the two opposite t because they cancel out to each other

6 + 7 - t - 4 = 0

Add and subtract

6 + 7 - 4 = 9

Thus:
9 - t = 0

Bring the 9 over to the 0 to isolate the -t

-t = 0 - 9

Calculate:

-t = -9

To get rid of the negative on the variable we have to divide it by -1 to make it positive bc negative divided by negative equals positive. Since we are dividing -1 to the -t we also have to divide -9 by -1.

t = 9


User Grifo
by
6.0k points